2013
DOI: 10.1253/circj.cj-12-0854
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between CHADS<sub>2</sub> Score and Efficacy of Antiarrhythmic Drug Therapy in Patients With Paroxysmal Atrial Fibrillation

Abstract: Background:The Cardiac failure, Hypertension, Age, Diabetes, Stroke [Doubled] (CHADS2) score is a useful scheme for risk stratification of thromboembolism patients, but there is little information about its usefulness for the evaluation of antiarrhythmic drug (AAD) therapy. Methods and Results:This study included 459 paroxysmal atrial fibrillation (AF) patients (309 men, mean age 66±12 years, mean follow-up 50±35 months) and prophylactic efficacy was analyzed on the basis of CHADS2 score.(1) Survival rates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Traditional clinical risk factors for recurrence include history of multiple AF episodes, use of diuretic treatment, higher CHADS-2 (congestive heart failure, history of hypertension, age≥75 years, diabetes mellitus, and past history of stroke or transient ischaemic attack doubled) index score, and frequent use of amiodarone, calcium-channel blockers, class 1C drugs and digitalis 30 31. Although each of these factors could predict AF recurrence with some accuracy, a quantitative combination of these predictors is not available, and the clinical utility of these variables remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional clinical risk factors for recurrence include history of multiple AF episodes, use of diuretic treatment, higher CHADS-2 (congestive heart failure, history of hypertension, age≥75 years, diabetes mellitus, and past history of stroke or transient ischaemic attack doubled) index score, and frequent use of amiodarone, calcium-channel blockers, class 1C drugs and digitalis 30 31. Although each of these factors could predict AF recurrence with some accuracy, a quantitative combination of these predictors is not available, and the clinical utility of these variables remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10 First, Saad et al 10 demonstrated that a CHADS 2 score ≥2 was a predictor for LRAF, which was later confirmed by several small studies. 7,18 Recently, Letsas et al 8 showed that both CHADS 2 and CHA 2 DS 2 -VASc scores are associated with rhythm outcomes after catheter ablation. In accordance to previous studies, they demonstrated that a score ≥2 for both CHADS 2 and CHA 2 DS 2 -VASc had the highest predictive value for AF recurrences (AUC, 0.644 and 0.627, respectively).…”
Section: Chads 2 and Cha 2 Ds 2 -Vasc Scores As Predictors For Af Recmentioning
confidence: 99%
“…7,10,18 Because the increased LA diameter or volume is considered as advanced structural remodeling, and persistent AF is rather an advanced disease stage with failing ability for self-termination, the association between AF recurrences and these clinical important markers is unsurprising. Recently, Chao et al 11 showed an association between electroanatomic LA remodeling and renal dysfunction.…”
Section: Renal Dysfunction and R 2 Chads 2 Score As Predictors For Afmentioning
confidence: 99%
“…The results of this study demonstrate that, compared to dronedarone, amiodarone, class 1C agents, and sotalol but not dofetilide, are more effective in preventing AF recurrence and AF-related hospitalizations. Our analysis showed that (1) amiodarone was the most effective agent in preventing AF recurrence despite a higher incidence of left ventricular dysfunction, CHF, and mean CHADS 2 score [21] in the amiodarone group; (2) the efficacy of class 1C agents and sotalol were superior to dronedrone, but as expected the class 1C agent patients had preserved myocardial function; (3) Patients in the sotalol and dronedarone groups had comparable degrees of left ventricular dysfunction and other baseline characteristics but outcomes were better with sotalol; and (4) the efficacy of dofetilide was similar to dronedrone but associated with fewer cardiac admissions. These conclusions were consistent among the different patient subgroups that we evaluated, except that the evidence for sotalol and class 1C agents was strongest for patients without structural heart disease.…”
Section: Discussionmentioning
confidence: 79%